2005
DOI: 10.1051/0004-6361:20042562
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and scattering by interstellar dust: an XMM-Newton observation of Cyg X-2

Abstract: We present results of the XMM-Newton observation of the bright X-ray binary Cyg X-2. In our analysis we focus on the absorption and scattering of the X-ray emission by interstellar dust distributed along the line of sight. The scattering halo around Cyg X-2, observed with the CCD detector EPIC-pn, is well detected up to ∼7 arcmin and contributes ∼5-7% to the total source emission at 1 keV, depending on the dust size distribution model considered. For the first time spatially resolved spectroscopy of a scatteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 49 publications
(89 reference statements)
5
71
1
Order By: Relevance
“…By assuming the model proposed by Vrtilek et al (1988), Kuulkers and collaborators found similar results but measured difference in EW, confirming that the shape of the feature, as well as its EW, changes from observation to observation. However, we note that both Chandra (Takei et al 2002) and XMM-Newton (Costantini et al 2005) observations of Cyg X-2 revealed a complex structure of absorption edges (due to a combination of N, O, Fe-L, and Ne-K shells) in the region 0.4-0.8 keV but no emission around 1 keV. Due to the high-energy resolution of these two satellites at low energy and since the occasional presence of a strong absorption edge, if not taken into account, may produce emission-like features in the residuals, we tried to use a single absorption edge in our best-fit models; the result was however unsatisfactory, since it required a Gaussian emission line.…”
Section: Observations and Data Analysismentioning
confidence: 69%
“…By assuming the model proposed by Vrtilek et al (1988), Kuulkers and collaborators found similar results but measured difference in EW, confirming that the shape of the feature, as well as its EW, changes from observation to observation. However, we note that both Chandra (Takei et al 2002) and XMM-Newton (Costantini et al 2005) observations of Cyg X-2 revealed a complex structure of absorption edges (due to a combination of N, O, Fe-L, and Ne-K shells) in the region 0.4-0.8 keV but no emission around 1 keV. Due to the high-energy resolution of these two satellites at low energy and since the occasional presence of a strong absorption edge, if not taken into account, may produce emission-like features in the residuals, we tried to use a single absorption edge in our best-fit models; the result was however unsatisfactory, since it required a Gaussian emission line.…”
Section: Observations and Data Analysismentioning
confidence: 69%
“…Absorption structure due to ionized gas and dust was found around the interstellar oxygen K-shell absorption edge in the spectra of several sources (Paerels et al 2001;de Vries et al 2003;Juett et al 2004;Costantini et al 2005Costantini et al , 2012Kaastra et al 2009;Pinto et al 2010Pinto et al , 2012a.…”
Section: Richter 2006)mentioning
confidence: 99%
“…Thirdly, X-ray observational data indicate that even though iron is present in interstellar dust it is not in Fe-rich silicates but in the form of metallic iron inclusions within Mg-rich silicates (e.g., Costantini et al 2005, Xiang et al 2011 Fourthly, and subsequent to the publication of the original Jones et al (2013) diffuse ISM dust model, seven particles of interstellar origin collected and analysed by the Stardust mission exhibit amorphous and crystalline grains and multiple iron-bearing phases, including metallic iron and iron sulphide (Westphal et al 2014). …”
Section: Amorphous Silicates A-silmentioning
confidence: 99%